Pengimplementasian kaedah multigrid terhadap empat kaedah lelaran terpilih bagi menyelesaikan persamaan resapan olakan satu dimensi. - Mi Yusuf, Lizawati; Abdullah, Abdul Rahman; Othman, Mohd. Shahizan (Penerbit UTM Press, 2003)

(untitled)
Multigrid method is one of the effective methods to solve complex and large size of linear equation problem. Multigrid methods have three processes, such as smoothing process, interpolation and restriction. In this research, Gauss-Seidel, Gauss-Seidel Red Black (GSRB), Jacobi and Succesive Over Relaxation (SOR) methods are used as smoother to solve one dimensional convection-diffusion equation. As a result, the research shows that solving with multigrid method is better than non multigrid method.